In-situ electrospun aligned and maize-like AgNPs/PVA@Ag nanofibers for surface-enhanced Raman scattering on arbitrary surface - Zhao, Xiaofei; Li, Chonghui; Li, Zhen; Yu, Jing; Pan, Jie; Si, Haipeng; Yang, Cheng; Jiang, Shouzhen; Zhang, Chao; Man, Baoyuan (Nanophotonics (Berlin, Germany), 2019)
An efficient electrospun aligned surface enhanced Raman scattering (SERS) and maize-like substrate of polyvinyl alcohol (PVA) composite and Ag colloid nanofibers decorated with thermal evaporated Ag nanoparticles (AgNPs) has been developed by taking advantage of electrostatic interactions. The synergistic effects of the evaporated AgNPs (niblets) and the Ag colloid in PVA (corncob) could arouse strong electromagnetic field between the lateral and vertical nanogaps which has been demonstrated by experiment and finite-different time-domain (FDTD) simulation. In this experiment, the aligned nanofibers possesses an excellent sensitivity by detection of crystal violet (CV) and malachite green (MG) molecule at low concentration. Moreover, the proposed flexible SERS sensor was measured with outstanding uniformity and reproducibility. We also carried out electrospinning on a curved surface to detect the mixture of Sudan I, CV and MG molecule, which demonstrates that flexible SERS sensor, has enormous potential in accurate and detection on the complex geometric structure.